Building the gerontological performance of nurses in Family Health Programs - Polaro, Sandra Helena Isse; Gonçalves, Lúcia Hisako Takase; Alvarez, Angela Maria (Revista da Escola de Enfermagem da USP, 2013)
The goal of this article is to analyze the development of gerontological nurses working in the Family Health Program in a municipal district in Belém, PA. Data have been collected through interviews with 14 nurses between 08/2009 and 02/2010 and have been analyzed using the content analysis method to generate topics. One such topic is the theme of this article: building gerontological work, and the sub-topics are the following: nursing consultation, home visits, family care, and seeking partnerships for integrated actions. According to the results, it may be inferred from nurses performing gerontological tasks that work is hampered primarily by urban violence, the inefficient functional structure of services and poor specific geriatric training. However, nurses have built a special "making of gerontology" by creating strategies of integrated actions according to each new situation that has been presented.